Messiah: Understanding and Performing Handel's Masterpiece - Rilling, Helmuth; Romey, Kathy Saltzman (Stuttgart Carus, 2015)
In collaboration with Kathy Saltzman Romey. The great choral conductor Rilling breaks down Handel's masterwork number by number, detailing his thoughts about performing and conducting the music. With a foreword by H. Royce Saltzman, preface, introduction, and appendix. Music examples.
Contains music examples from the edition by Ton Koopman and Jan Siemons
Includes bibliographical references (pages 127-128).
Helmuth Rilling ; in collaboration with Kathy Saltzman Romey.
Keywords: Handel, George Frideric -- 1685-1759; Jennens, Charles -- 1700-1773; 18th Century (1701-1800); Messiah; Musical interpretation; Performance; Oratorio; Dublin (Ireland)